(Can't Get No) Neighborhood Satisfaction? How Multilevel Immigration Factors Shape Latinos' Neighborhood Attitudes. (May 2020) - Schachter, Ariela; Sharp, Gregory; Kimbro, Rachel T.
How does immigrant generation shape Latinos' neighborhood attitudes? We extend theoretical frameworks focused on neighborhood attainment to explore how immigrant generation structures Latinos' neighborhood satisfaction, particularly with respect to neighborhood immigrant composition. Using longitudinal data from the Los Angeles Family and Neighborhood Survey, we estimate fixed-effects regression models to examine the associations between self-reported neighborhood satisfaction and changes in neighborhood immigrant composition. We find that first-generation Latino immigrants tend to react more positively to growing immigrant populations in their neighborhoods compared to 1.5-generation and native-born Latinos; these differences are most pronounced in more socioeconomically advantaged neighborhoods. We consider the implications of these attitudinal differences for understanding the mechanisms of Latino residential segregation and neighborhood attainment.